2005
DOI: 10.1128/jcm.43.12.5957-5962.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a (1→3)-β- d -Glucan Assay for Diagnosis of Invasive Fungal Infections

Abstract: The Fungitell assay (Associates of Cape Cod, Inc.) is a commercial test that detects (1-3)-␤-D-glucan (BG) and is intended for diagnosis of invasive fungal infections. To evaluate the Fungitell assay, we tested serum and plasma samples from healthy blood donors and from patients with blood cultures positive for yeast or bacteria. All 36 blood donors were BG negative, and 13 of 15 candidemic patients were BG positive. Of 25 bacteremic patients, 14 (10 with gram-positive bacteremia) were BG positive. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
244
4
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(260 citation statements)
references
References 35 publications
4
244
4
5
Order By: Relevance
“…2 Prediction rule for the diagnosis of invasive candidiasis (IC) in nonneutropenic adult critically ill patients with severe abdominal conditions. Each terminal node shows the probability of the predicted event intravenous immunoglobulins, albumin, coagulation factors, and plasma protein fractions [27][28][29]. In addition, Pickering et al [29] showed in a cross-contamination experiment that excess manipulation of a sample can result in its contamination with BDG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Prediction rule for the diagnosis of invasive candidiasis (IC) in nonneutropenic adult critically ill patients with severe abdominal conditions. Each terminal node shows the probability of the predicted event intravenous immunoglobulins, albumin, coagulation factors, and plasma protein fractions [27][28][29]. In addition, Pickering et al [29] showed in a cross-contamination experiment that excess manipulation of a sample can result in its contamination with BDG.…”
Section: Discussionmentioning
confidence: 99%
“…Each terminal node shows the probability of the predicted event intravenous immunoglobulins, albumin, coagulation factors, and plasma protein fractions [27][28][29]. In addition, Pickering et al [29] showed in a cross-contamination experiment that excess manipulation of a sample can result in its contamination with BDG. In our IC patients, 12 (38.7 %) had renal replacement therapy, 3 (9.6 %) had Gram-positive bacteremia, and 3 (9.6 %) received betalactam antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some conditions such as exposure to certain gauzes [25], taking several antibiotics at high concentrations [26], using certain hemodialysis cellulose membranes [27], and receipt of albumin or immunoglobulin products, plasma proteins or coagulation factors [28] may contribute to a greater yield of false positive. False positives by BDG may also be obtained by a variety of other reasons including "bacteremia, hemolysis; intravenous administration of treatment with certain medications; exposure to cotton bandages; heat stroke; and unknown causes" [29,30]. The use of different species of horseshoe crab as a source of reagent by the manufacturers creates different cutoff values.…”
Section: Discussionmentioning
confidence: 99%
“…This antigen can be detected in serum and other body fluids. It has been shown that BG can be positive before the clinical symptoms and radiological signs [14][15][16][17][18][19][20]. Various studies show that this test's sensitivity and specifity varies between 55-95% and 77-96%, respectively [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%